2003
DOI: 10.1303/aez.2003.203
|View full text |Cite
|
Sign up to set email alerts
|

Importance of social stimuli for the development of learning capability in honeybees

Abstract: The learning ability of the European honeybee, Apis mellifera, is well known. However, in a proboscis-extension reflex (PER) assay, newly emerged and very young worker bees could not associate a given odor (conditioned stimulus, CS) with a sucrose reward (unconditioned stimulus, US): This ability was acquired 5 to 9 days after emergence in workers, while it was accomplished 2 to 5 days after emergence in drones, probably reflecting the earlier onset of flight in drones. When workers are reared individually in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…The findings presented above add to the body of evidence on the pervasive influence of the social environment on the behavior and physiology of honey bees Ichikawa and Sasaki, 2003;Maleszka et al, 2009). The social manipulations reported here also influenced the development of circadian rhythms in the same young honey bees .…”
Section: Research Articlesupporting
confidence: 59%
“…The findings presented above add to the body of evidence on the pervasive influence of the social environment on the behavior and physiology of honey bees Ichikawa and Sasaki, 2003;Maleszka et al, 2009). The social manipulations reported here also influenced the development of circadian rhythms in the same young honey bees .…”
Section: Research Articlesupporting
confidence: 59%
“…Dopamine is also implicated in aversive learning with punishment and blocking dopamine receptors is reported to suppress aversive learning (Vergoz et al., 2007). Although developmental changes in aversive learning in honeybee are not well known, the appetitive learning abilities of workers and drones have been shown to increase during one week after their emergence (Ichikawa and Sasaki, 2003). It is also assumed that foragers have a higher information processing ability than nurses from the differences in behavioral complexity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the observed percentage (68%) of CRs, it is reasonable to assume that both foragers and younger bees acquired longterm olfactory memories, though the relative proportions of both groups remain unknown and their particular learning performances cannot be compared. Indeed, both foragers and younger bees learn olfactory cues under controlled laboratory conditions (Ray & Ferneyhough 1999;Ichikawa & Sasaki 2003). It has been recently reported that trophallaxis, the exchange of liquid food by mouth (Wilson 1971), allows bees to learn nectar scents and leads to longterm olfactory memories under controlled laboratory conditions, i.e.…”
Section: Discussionmentioning
confidence: 99%